Urgensi Pembentukan Badan Usaha Milik Desa Di Desa Gisik Cemandi Kecamatan Sedati Kabupaten Sidoarjo - Anastasia, Bella Wanda; Anggraini, Berliana Aji; Fitriana, Nur; Wibawani, Sri (Syntax Idea, 2021)
Gisik Cemandi Village, Sedati districts is a village located in the coastal area of Sidoarjo Regency. This geographical condition has resulted in the hamlet of Gisik Cemandi having abundant natural resources and economic potential so that it can be developed and utilized as a business unit in the form of BUMDesa. The formation of a BUMDesa has a significant role to play in accelerating the economic development of Gisik Cemandi Village in realizing an independent village and a more prosperous community. However, due to several social problems, the formation of BUMDesa in Gisik Cemandi Village has not yet been realized. This study aims to determine the urgency of establishing BUMDesa in Gisik Cemandi Village through SWOT analysis (Strengths and Opportunities also Threats and Weakness). The method used in this research is descriptive qualitative. The results of the study describe the formation of BUMDesa in the village of Gisik Cemandi, Sedati sub-district, Sidoarjo district, which is very much needed based on a SWOT analysis, which shows that the formation of Bumdesa is crucial to support the welfare of the village community and the economic sustainability of the village of Gisik Cemandi.